2018
DOI: 10.1007/s10903-018-0755-0
|View full text |Cite
|
Sign up to set email alerts
|

Recruiting Filipino Immigrants in a Randomized Controlled Trial Promoting Enrollment in an Evidence-Based Parenting Intervention

Abstract: Filipinos, the second largest Asian subgroup in the U.S., experience significant youth behavioral health disparities but remain under-represented in health research. We describe lessons learned from using the Matching Model of Recruitment to recruit 215 Filipinos to participate in a large, randomized controlled trial of a culturally tailored video aimed at increasing enrollment in the Incredible Years® Parent Program. We recruited participants from schools, churches, clinics, community events, and other commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 19 publications
(34 reference statements)
0
22
0
Order By: Relevance
“…In the weWomen study, we reimbursed our collaborators to conduct intensive recruitment efforts and engaged the community through snowball sampling techniques. Researchers found the importance of engaging community members to develop social connections and cultivate trust (Burnette & Sanders, 2014; Buseh et al, 2017; Hernandez et al, 2019; Javier et al, 2019; Reiss et al, 2014). Community advisory boards have also been found to be highly effective in establishing the engagement of the community to not only maximize recruitment efforts but also build long-term relationships (Javier et al, 2019; Njie-Carr, Jones-Parker, Massey, Baker, & Nganga-Good, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the weWomen study, we reimbursed our collaborators to conduct intensive recruitment efforts and engaged the community through snowball sampling techniques. Researchers found the importance of engaging community members to develop social connections and cultivate trust (Burnette & Sanders, 2014; Buseh et al, 2017; Hernandez et al, 2019; Javier et al, 2019; Reiss et al, 2014). Community advisory boards have also been found to be highly effective in establishing the engagement of the community to not only maximize recruitment efforts but also build long-term relationships (Javier et al, 2019; Njie-Carr, Jones-Parker, Massey, Baker, & Nganga-Good, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…While written study recruitment materials in the languages of participants were found to propagate enrollment, this strategy failed to address mistrust of researchers, which was an important barrier in studies with hidden populations (Ibrahim & Sidani, 2014). Therefore, community partnerships and collaborations are important to develop trust, including the engagement of key stakeholders and leaders from the community (Choi, Heo, Song, & Han, 2016; Gabriel et al, 2017; Hernandez et al, 2019; Javier et al, 2019; Katigbak et al, 2016; Njie-Carr, Jones-Parker et al, 2018; Sheehan et al, 2016; Wang, 2014). In addition, we trained bicultural and bilingual team members to support recruitment efforts, which is consistent with other studies (Blanchet et al, 2017; Choi et al, 2016; Lara-Cinisomo, Plott, Grewen, & Meltzer-Brody, 2016; Reiss et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies were qualitative (n = 20) [26,31,39,42,49,57,68,[70][71][72][73][74][75][76][77][78][79][80][81][82] and RCT studies (n = 18) [ 23,34,36,38,44,58,64,[83][84][85][86][87][88][89][90][91][92][93]. A total of 14 of the studies lacked a clear methods section or the methods were inadequately reported [27,28,30,32,33,45,55,56,59,66,[94][95][96]…”
Section: Characteristics Of the Selected Studiesmentioning
confidence: 99%
“…In addition, studies also recruited participants from public services e.g. kindergarten[55,64,70,76], schools[29, 30, 32, 33, 37, 38, 40, 56, 58, 72, 80, 84-87, 90, 94, 95, 104], language schools[73,74,107,108], churches or religious organisations[80,94,105,109,110], social services, or through social worker[29,38,[84][85][86][87]104], child welfare services[84], health care clinics[36,44,50,54,55], mental health services or through mental health worker[44,49,50,58,71,85,104,105], initial registration centre…”
mentioning
confidence: 99%
“…Passive recruitment may not be effective for minoritized communities, including AsA, given barriers to research participation that disproportionately affect these groups, such as warranted mistrust of academic and healthcare institutions, linguistic mismatch, and time constraints (Katigbak et al, 2016;David et al, 2010). Instead, experts propose leveraging community-research partnerships (e.g., Collins et al, 2018;Lau et al, 2010) that actively consider the broader, converging socio-political factors impacting research engagement in minoritized communities (e.g., Matching Model of Recruitment; Javier et al, 2019). Once participants are successfully recruited, research practices (e.g., consent procedures, participant payment rates and transactions, assessment and data collection procedures) should be carefully audited and modified in collaboration with community members.…”
Section: Enhance Cultural Responsiveness Of Research Practicesmentioning
confidence: 99%